Evaluasi Proses Belajar Dari Rumah (BDR) Pada Masa Pandemi Covid-19 di SDN 1 Setanggor dan SDN 2 Setanggor - Wijaya, Wawan Pratama; Asrin; Lalu Hamdian Affandi (Pendagogia: Jurnal Pendidikan Dasar, 2022)
The Corona Virus Disease (COVID-19) pandemic attacks anyone so the government must take a stand in preventing wider transmission, including the education sector. The Ministry of Education and Culture created a learning from home program or BDR during the pandemic and issued several circulars regarding policies for implementing learning from home during the COVID-19 emergency. This study is to evaluate the learning process from home during the pandemic at SDN 1 Setanggor and SDN 2 Setanggor related to the implementation, the role of people and the barriers of teachers and parents of students while studying from home so far. In this study, there were 8 teachers and 12 guardians of students in each school as respondents. The results of this study obtained from observations, interviews and documentation that the implementation of learning from home cannot be carried out optimally due to the lack of teacher preparation and inadequate infrastructure. Another obstacle also comes from parents who cannot be optimal in assisting children to learn from home. Another teacher's complaint was also because of the implementation of learning from home, students did not understand the content of the material.